Coach leadership effect on elite handball players' psychological empowerment and organizational citizenship behavior - Lee, Y.; Kim, S.; Kang, J. (International Journal of Sports Science and Coaching, 2013)
This article examines the significance of the correlation between coach leadership behavior and players' organizational citizenship behavior, and the mediating role of psychological empowerment in the process. A total of 73 professional handball players from five different teams assessed leadership style, psychological empowerment, and organizational citizenship behavior based on the scale adapted from Multifactor Leadership Questionnaire form 5X. Regression analysis and bootstrap methods were utilized to test the proposed hypotheses. Findings indicated that both transactional and transformational leadership styles significantly predicted players' organizational citizenship behavior. In particular, psychological empowerment played a mediating role in the association between coach leadership and organizational citizenship behavior.